Recognition and enforcement of judgments in employment matters in EU private international law - Grusic, Ugljesa (Taylor & Francis, 2016)
This article deals with the recognition and enforcement of judgments in employment matters in European private international law. After looking into the theoretical underpinnings of the protection of employees by rules of recognition and enforcement of foreign judgments, this article examines the recognition and enforcement of judgments concerning individual employment contracts under the Recast of the Brussels I Regulation, the European Enforcement Order Regulation and the European Order for Payment Procedure Regulation. It is shown that the lack of a jurisdictional defence for employment disputes in the latter two instruments has the potential to undermine, at the overlap of the fields of application of these instruments and the Brussels I Recast, the protection offered to employees by the Recast’s jurisdictional defence.